Evolution of Increased Photosynthetic Capacity and Its Underlying Traits in Invasive Jacobaea vulgaris - Lin, Tiantian; Klinkhamer, Peter G. L.; Pons, Thijs L.; Mulder, Patrick P. J.; Vrieling, Klaas (Frontiers in Plant Science, 2019)
The Evolution of Increased Competitive Ability (EICA) and the Shifting Defense Hypothesis (SDH) predict that evolutionary changes occur in a suite of traits related to defense and growth in invasive plant species as result of the absence of specialist herbivores. We tested how this suite of traits changed due to the absence of specialist herbivores in multiple invasive regions that differ in climatic conditions and we expected these traits to show similar changes in all invasive regions. We examined (i) plant growth and its underlying traits, such as photosynthetic capacity, (ii) regrowth-related traits, such as carbohydrate storage and (iii) plant qualitative defense, such as pyrrolizidine alkaloids (PAs) in native and invasive genotypes of Jacobaea vulgaris in a controlled environment. Our results show that invasive J. vulgaris genotypes have evolved a higher photosynthetic rate and total PA concentration but a lower investment in root carbohydrates, which supports the SDH hypothesis. All the traits changed consistently and significantly in the same direction in all four invasive regions, indicative of a parallel evolution. Climatic variables did differ between ranges but did not correlate with traits values, suggesting that climatic changes can be largely ruled out as a selective force on these traits.